Post‐infectious IBS: Defining its clinical features and prognosis using an internet‐based survey. Issue 8 (1st October 2018) - Card, Tim; Enck, Paul; Barbara, Giovanni; Boeckxstaens, Guy EE; Santos, Javier; Azpiroz, Fernando; Mearin, Fermin; Aziz, Qasim; Marshall, John; Spiller, Robin
Abstract : Background: Gastrointestinal infection is an important risk factor for developing irritable bowel syndrome (IBS). Our aim was to characterise post‐infectious IBS (PI‐IBS) compared to other IBS patients. Methods: An internet survey of IBS patients using Rome III diagnostic questionnaire, Hospital Anxiety and Depression Scale (HADS) and Patient Health Questionnaire‐12 Somatic Symptom (PHQ12‐SS) scale score documenting the mode of onset was conducted. Results: A total of 7811 participants (63.2% female), of whom 1004 (13.3%) met criteria for PI‐IBS, were studied. Seventy per cent of PI‐IBS patients described sudden onset, 35% onset while travelling, 49.6% vomiting, 49.9% fever and 20.3% bloody diarrhoea. Compared to other IBS individuals, PI‐IBS was significantly associated with living in Northern Europe and North America, having a hysterectomy, not having an appendicectomy, higher PHQ12‐SS score and having more than one toilet in the family home. PI‐IBS patients had more frequent stools. At one year recovery rate in the PI‐IBS and non‐PI‐IBS group was 19.7% and 22.2%, p  = 0.15. Recovery rates were lower for females (20.7%) vs males (38.8%), those with somatisation (23.0%) vs those without (33.2%) and those living in North America or Northern Europe (21.1%) vs living elsewhere (33.9%) p  ≤ 0.001. Conclusion: PI‐IBS accounts for around 13% of all IBS in this internet sample, with some distinctive features but a similar prognosis to the remainder.